Integrated disposal waste management system a case study of Majlis Daerah Simpang Renggam at the state of Johor / Normala Yahaya, Enida Daud and Noor Aziza Anuar - Yahaya, Normala; Daud, Enida; Anuar, Noor Aziza (2006)
In Malaysia, the local authority have been responsible for solid waste management services. However, over the years, various weaknesses in the local authority implementation aspect, financial and technical aspects, have fed to inefficiency in the providing the services to the people alike. The increasing waste generation and the least environmental awareness among the general public increase the burden to the local authority. To reduce the burden, the privatization process was initiated in 1996 with the aim of attaining an efficient management system to enhance environmental quality through resource, re-use and waste minimization. However, the negative attitude of the people towards a number of waste management issues that may hinder the implementation of effective privatized solid waste management options. This project which is part of the fulfillment for an Executive Master of Business Administration at the University of Technology MARA, Malaysia, is trying to unveil the strategic management of waste disposal of local authority in a small town of Simpang Renggam which is 70km from the city of Johor Bahru, Malaysia. The scope of the study was mainly on the general solid waste management and activities, and the related parties. As the Malaysian has moved towards an integrated approach to solid waste management rather than reliance on a single method, therefore it has begun to look to other, more experienced countries such. as Japan, Singapore, USA and Holland to provide models for structuring integrated systems. The purpose of this study was to evaluate Malaysia's integrated solid waste management systems, giving special attention to, and performing close analysis of its sanitary landfill and other related technique like re-cycling activity. In addition, this study focused on the environmental regulatory setting within which these solid waste management activities are conducted.